Natural disasters and banking stability - Hassan Alalmaee (Economies, 2023)
This paper aims to examine the impact of natural disasters on banking stability across different levels of economic development. Utilizing bank-level data from 1242 banks in 72 countries, combined with natural disaster data from the Center for Research on the Epidemiology of Disasters, we contribute to the literature in three ways. Firstly, we directly assess the influence of natural disasters on banking stability. Secondly, we focus on bank-level data instead of country-level data. Thirdly, we expand on existing research by using different thresholds for the total number of people affected to population ratio, surpassing the previously suggested threshold of 0.5%. Our panel regression analysis with banks and year-fixed effects reveals that natural disasters significantly affect bank stability, particularly in middle- and low-income countries. These effects are robust across alternative measures and estimations, leading to higher non-performing loans, lower return on assets, and decreased capital and return on equity ratios, indicating a negative impact on bank performance.
Keywords: 330; natural disasters; banking stability; bank performance; financial development; climate